Degradation of Red Ferralitic (Rhodic Ferralsol) soils grown with tobacco (Nicotiana tabacum L.) in the Artemisa province, Cuba (2017)
“Partido” is a tobacco growing area which extends for some 3000 hectares among the municipalities of San Antonio de los Baños, Güira de Melena and Alquízar in the Cuban province of Artemisa. Predominant soils are Red Ferralitic (Rhodic Ferralsol according to the World Reference Base), with a strong tendency to alkalinization which has a negative impact on the quality of their agricultural use. The aim of this research was to quantify the geographical extension of the degradation process, to determine how deep it happens along the soil profile and to establish its possible relationship with the quality and quantity of water applied to tobacco fields. The chemical, physical and mineralogical analyses of two test pits carried out in the area were compared: one profile without agricultural use with one characteristic soil profile under continuous production. After being subjected to the same irrigation regime in laboratory conditions, it was concluded that degradation affects to 89.56% of the area of tobacco soils evaluated. This phenomenon occurs very deeply along the soil profile and happens downwards, causing the accumulation of calcium and the loss of sodium and potassium in the superficial horizon, what is shown in pH rises. Such processes, associated to irrigation water and to insufficient rainfall regime which are traditional in the territory, have led to changes in the mineralogical composition of these tobacco soils appearance of minerals such as gibbsite which was absent in uncultivated Red Ferralitic soils, which involve the modification of soil classification at gender level.